2009
DOI: 10.1016/j.ijgo.2009.08.014
|View full text |Cite
|
Sign up to set email alerts
|

Resumption of sexual activity and regular menses after childbirth among women infected with HIV in Malawi

Abstract: HIV-infected women need adequate counseling to take into account their HIV infection status before resuming sexual activity after childbirth.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
10
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 22 publications
(25 reference statements)
7
10
0
Order By: Relevance
“…Qualitatively, women reported that sexual activity should cease between the 6 th and 8 th month of pregnancy and not resume until 6 months postpartum. This corroborates with a recent study about postpartum abstinence in Malawi reporting that the median time to resumption of sexual activity after childbirth was between 7 and 9 months [20]. In our study, reports of spouse’s risky behavior did not differ between groups.…”
Section: Discussionsupporting
confidence: 93%
“…Qualitatively, women reported that sexual activity should cease between the 6 th and 8 th month of pregnancy and not resume until 6 months postpartum. This corroborates with a recent study about postpartum abstinence in Malawi reporting that the median time to resumption of sexual activity after childbirth was between 7 and 9 months [20]. In our study, reports of spouse’s risky behavior did not differ between groups.…”
Section: Discussionsupporting
confidence: 93%
“…Recent studies from Nigeria report earlier resumption of coitus after delivery 15,24 . We found that older married women reported earlier resumption of sex, consistent with other studies 15,46-48 . In our study, women with caesarean deliveries resumed sex earlier compared to those delivered vaginally.…”
Section: Discussionsupporting
confidence: 92%
“…E-mail: anyi_ ezebialu@yahoo.com with dyspareunia (Signorello et al 2001). A study of HIV-positive women in Malawi indicated that resumption of coitus is dependent on certain sociodemographic characteristics such as marital status and use of contraceptives (Makanani et al 2010).…”
Section: Introductionmentioning
confidence: 99%